Analysis of Intentionally Structured Programs to Improve Life Skills Through Out of School Activities - Ari Gana Yulianto; Yudy Hendrayana; Agus Mahendra (JUARA : Jurnal Olahraga, 2023)
Life skills are one of the components in forming positive youth development. The purpose of this research is to find out intentionally structured programs that are widely used to improve life skills through out-of-school activities, to find out about out-of-school programs used to enhance life skills which are included in intentionally structured programs and to find out the results of intentionally structured programs on improving life skills through out of school activities, the research method in this study used systematic literature review which is a literature review method that identifies, assesses, and interprets all findings on a research topic, to answer predetermined research questions. In this study, researchers used 30 Final Paper journals to review 210 journals taken from 4 databases: Taylor & Francis, Google Scholar, Science Direct, and Sage. The results showed that participation in structured school activities programs was intentional in its application. Can produce quality programs where this can contribute to youth development in a positive direction. This shows that the Intentionally structured program that is implemented in out-of-school activities in its implementation can influence positive youth development; this can be seen from the increase in the elements 5C elements in (PYD) namely Competence, Confidence, Connection, Character and Caring Or Compassion.